2007
DOI: 10.1007/s10750-006-0352-4
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and interannual variability in the taxonomic composition and production dynamics of phytoplankton assemblages in Crater Lake, Oregon

Abstract: Taxonomic composition and production dynamics of phytoplankton assemblages in Crater Lake, Oregon, were examined during time periods between 1984 and 2000. The objectives of the study were (1) to investigate spatial and temporal patterns in species composition, chlorophyll concentration, and primary productivity relative to seasonal patterns of water circulation; (2) to explore relationships between water column chemistry and the taxonomic composition of the phytoplankton; and (3) to determine effects of prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 30 publications
1
3
0
1
Order By: Relevance
“…Phytoplankton community composition during summer varied vertically within the water column in both high and low nutrient years similar to previous studies (McIntire et al, 2007). Overall, the epilimnion (above & 20 m) was dominated by diatoms and dinoflagellates, whereas deeper depths had higher diversity (Fig.…”
Section: Phytoplankton Taxonomysupporting
confidence: 84%
See 2 more Smart Citations
“…Phytoplankton community composition during summer varied vertically within the water column in both high and low nutrient years similar to previous studies (McIntire et al, 2007). Overall, the epilimnion (above & 20 m) was dominated by diatoms and dinoflagellates, whereas deeper depths had higher diversity (Fig.…”
Section: Phytoplankton Taxonomysupporting
confidence: 84%
“…Boss et al (2007) demonstrated that Fchl and Chl-a were highly correlated in Crater Lake, with the exception of reductions in near-surface values during daytime due to non-photochemical quenching. Laboratory Chl-a samples were determined from 17 depths (0-300 m) via extraction using 0.45 lm filters with acetone and a Turner designs Model 10 fluorometer (McIntire et al, 2007). Net primary productivity was estimated at 13 depths (0-180 m), using the carbon-14 light-dark bottle method with a 4 h midday incubation time, 0.45 lm filters, and counted in a Beckman Liquid Scintillation Counter (McIntire et al, 2007).…”
Section: Long-term Datamentioning
confidence: 99%
See 1 more Smart Citation
“…More thoroughly assessing the role of watershed factors in moderating or amplifying lake responses will help us quantify which lakes are more resistant or resilient to environmental change. Our study did not model biological interactions, but future investigators should consider the role of top‐down influences and trophic interactions (McIntire et al 2007, Ellis et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Vários trabalhos descrevem a estrutura da comunidade fitoplanctônica em reservatórios brasileiros. Dentre eles, destacam-se os trabalhos de DOS SANTOS e CALIJURI, 1998;BOUVY et al, 2000;FIGUEREDO e GIANI, 2001;CALIJURI et al, 2002;FALCO e CALIJURI, 2002;RAMIREZ e BICUDO, 2002;TUCCI e SANT'ANNA, 2003;SILVA et al, 2005;TRAIN et al, 2005;MOURA et al, 2007;BORGES et al, 2008;CROSSETTI et al, 2008;DELLAMANO-OLIVEIRA et al, 2008;BECKER et al, 2009; FIGUEREDO e GIANI, 2009 e em outros países os de McINTIRE et al, 2007;SALMASSO e PADISÁK, 2007;CABECINHA et al, 2009; CUNHA e CALIJURI, 2011; CUNHA, 2012.…”
Section: Revisão Bibliográficaunclassified